Pengaruh model pembelajaran kooperatif tipe think talk write (TTW) terhadap kemampuan pemecahan masalah matematika siswa kelas XI MIA SMA NW Mataram Tahun Pelajaran 2019/2020 - Aena Malini; Nurul Hikmah; Wahidaturrahmi Wahidaturrahmi; Laila Hayati (Griya Journal of Mathematics Education and Application, 2021)
This research aims to determine the effect of Think Talk Write (TTW) cooperative learning model towards the ability of mathematics problem solving of grade XI MIA SMA NW Mataram academic year 2019/2020. Type of the research is a quasi-experimental design with a posttest only control design. The population of the research is all students grade XI MIA SMA NW Mataram academic year 2019/2020. The sampling technique was saturated sampling tecnique, so the sample obtained that XI MIA 1 as the experimental class and XI MIA 2 as the controlling class. The instrument used was a test of the students learning achievement (post-test) on the sequence and series material. Quantitave analysis obtained by using t-test. The result of this research showed that there is a difference in the average score of students who get learning use the Think Talk Write (TTW) cooperative learning models with students who use direct learning. Meanwhile the effect of Think Talk Write (TTW) cooperative learning model towards the ability of mathematics problem solving of using the effect size with moderate category. This means that the Think Talk Write (TTW) type of cooperative learning models is quite influential on the mathematics problem solving ability of grade XI MIA SMA NW Mataram.